Osteoporosis prevention and osteoporosis exercise in community-based public health programs - Vu H. Nguyen (Osteoporosis and Sarcopenia, 2017)
Osteoporosis is a serious public health concern worldwide, and community-based public health programs that increase osteoporosis preventive behaviors are ideal to combat this major public health issue. A review of community-based public health programs for osteoporosis prevention show that programs vary in numerous ways and have mixed results in increasing osteoporosis preventive behaviors, although most programs have had success in significantly increasing calcium intake, only a few programs have had success in significantly increasing weight-bearing exercise. Regarding calcium intake, all community-based public health programs that implemented: 1) at least one theoretical behavior change model, such as the health belief model, or 2) bone mineral density (BMD) testing for osteoporosis screening, have shown success in significantly increasing calcium intake. As community-based public health programs for osteoporosis prevention have shown limited success in increasing weight-bearing exercise, an additional review of community-based public health programs incorporating osteoporosis exercise showed that they have high compliance rates to increase weight-bearing exercise, but require high-intensity weight-bearing exercise of 80–85% 1-repetition maximum to significantly increase BMD to prevent osteoporosis. In the prevention of osteoporosis, for community-based public health programs to be most effective, they should implement theoretical behavior change models and/or BMD testing for osteoporosis screening, along with high-intensity resistance training. Recommendations for future research to further study effective community-based public health programs are also provided.